Thomas Hovenden : his life and art - Terhune, Anne Gregory (University of Pennsylvania Press, 2006)
Cover; Title; Copyright; Contents; Publisher's Note; List of Illustrations; Foreword; Chapter 1. Becoming an Artist; Chapter 2. From "Picturesque" Brittany to Paris: Painting Courage and Romance in History and Legend; Chapter 3. "What Shall American Artists Paint?"; Chapter 4. Painting the "Good Ole Times": Scenes of African American Life; Chapter 5. Images to "Appeal to the National Mind"; Chapter 6. Home Life: Center of "Our Joys or Sorrows"; Conclusion; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; P; Q; S; T; U; V; W; Y